2007
DOI: 10.1007/s12040-007-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Fairweather atmospheric electricity at Antarctica during local summer as observed from Indian station, Maitri

Abstract: Surface measurements of the atmospheric electrical parameters like Maxwell current, electric field and conductivity studied at the Indian station, Maitri (70.75 • S, 11.75 • E, 117 m above mean sea level), Antarctica, during austral summer have been analyzed for the years 2001 to 2004. A total of 69 days were selected which satisfied the 'fairweather' conditions, i.e., days with absence of high winds, drifting or falling snow, clouds, and fog effects. The diurnal variation curve of electric field and vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…It can be readily observed that E is highly dependent on local variation of atmospheric conductivity compared to J z . This is the reason why the variation of J z is often treated as the representative of ionospheric potential over E. Nevertheless, there are evidences of global signatures in measurements of vertical potential gradient in fair-weather in remote locations, far from sources of pollution, and during fair-weather conditions (Frank-Kamenetsky et al 2001;Reddell et al 2004;Burns et al 2005;Panneerselvam et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It can be readily observed that E is highly dependent on local variation of atmospheric conductivity compared to J z . This is the reason why the variation of J z is often treated as the representative of ionospheric potential over E. Nevertheless, there are evidences of global signatures in measurements of vertical potential gradient in fair-weather in remote locations, far from sources of pollution, and during fair-weather conditions (Frank-Kamenetsky et al 2001;Reddell et al 2004;Burns et al 2005;Panneerselvam et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Panneerselvam et al . [] presented another set of results on the diurnal variation of the PG and Maxwell current density. In their report, the mean diurnal variations were obtained from 69 fair‐weather days from the austral summer months distributed as 10, 12, 10, and 37 numbers of days during the years 2001–2004, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed neither a peak PG at ~13 UT observed by Deshpande and Kamra [] nor a depression in the prenoon hours observed by Panneerselvam et al . [] and Jeeva et al . [].…”
Section: Introductionmentioning
confidence: 99%
“…2A (Weimer, 2005;Anil Kumar et al, 2009;Tinsley 1996, Rycroft et al, 2012. In an earlier work, Panneerselvam et al, (2007b) mathematically differentiated later contributions from Maitri observations. It is well known that the current density J z is proportional to the overhead ionospheric potential (V i ).…”
Section: Current Densitymentioning
confidence: 99%
“…Deshpande and Kamra (2001) reported the data for 34 days in 1997. Panneerselvam et al (2007b) analyzed the data in 2001-2004. Using the rainfall data obtained from different…”
Section: Introductionmentioning
confidence: 99%